Best Recommended Exercise for patients with Hypertension - Tri Tjahjono, Cholid; Lestari, Defyna; Arthamin, Maimun (Universitas Brawijaya, 2023)
Hypertension is known as a fatal yet preventable risk factor for cardiovascular disease and is responsible for majority of cardiovascular mortality. Hypertension is closely associated with sedentary lifestyle. Physical activity and/or exercise are shown to retard development of hypertension. Exercise, combined with other measures of lifestyle behaviour and pharmacologic treatments, is recommended as an effective lifestyle behaviour for adults to prevent and treat hypertension. The current exercise prescription for the treatment of hypertension is: cardiovascular mode, for 20-60 minutes, 3-5 days per week, at 40-70% of maximum oxygen uptake (VO2(max)).. Both aerobic and resistance exercise, should be performed simultaneously by hypertensive patients. Aerobic activity could include walking, jogging, cycling, rowing swimming. While dynamic resistance training could include free weights, resistance machines, and resistance bands. Functional exercises should be comprised of step-ups, bodyweight exercises, and balance training. After an exercise session, BP decreases, and this decline continues for up to 24 h; which is called post-exercise hypotension. Overall 5 mmHg decrease in BP with regular exercise may be encouraged. With a decrease of 5 mmHg in systolic BP, mortality due to coronary artery disease decreases by 9%, mortality due to cerebrovascular accident decreases by 14% and all-cause mortality decreases by 7%. Regular exercise should therefore be recommended for all individuals including normotensives, pre-hypertensives, and hypertensives.